Analisis Satire dalam Program "In My Sotoy Opinion" di Narasi TV pada Bulan Februari Tahun 2022: Satire Analysis in "The In My Sotoy Opinion" Program on Narasi TV in February 2022 - Fitriyatullaili, Fitriyatullaili; Putikadyanto, Agus Purnomo Ahmad; Efendi, Agik Nur; Effendy, Moh Hafid (Kibas Cenderawasih, 2023)
Satire is a style of language that is used to satirize someone about something or the form of argument given by someone which often invites laughter. This article aims to find out the form of satire In My Sotoy Opinion program on Narasi TV in Februari 2022. This research uses a descriptive qualitative approach. The data from this study are transcripts of satirical utterances from YouTube in My Sotoy Opinion program on Narasi TV in Februari 2022. Data collection techniques used download, listening, and note-taking techniques, while data analysis in this study was carried out by identifying data, data classification, and data description. The results of the study show that the satirical sentences uttered by Devan Yulio Setiawan as the host of this program generally discuss social phenomena that are being discussed virally on social media. It can be concluded that the majority is dominated by satire in the form of irony. The findings of satire in the In My Sotoy Opinion Program form an attraction to the audience because it is motivational content that has a different concept from motivational content in general.